Overall Diversity Of Fruit-Feeding Butterflies (Lepidoptera: Nymphalidae) Along Vertical Gradient In A Peat Swamp Forest, Kota Samarahan, Sarawak - Christharina, Saurin Gintoron; Fatimah, Abang (Universiti Malaysia Sarawak, (UNIMAS), 2014)
A study which aims to investigate the vertical distribution pattern of nymphalids had been conducted in a peat swamp forest of Kota Samarahan, Sarawak. This 60-day sampling period which utilised baited traps as the main sampling method, had resulted to 104 individuals from both ground and canopy levels. The lower stratum revealed a higher diversity index (H’= 1.17466) in comparison with the canopy stratum. Nymhalinae represents the most diverse subfamily at both levels, dominating almost half of the total individuals respectively. In general, species richness and abundance decrease with the increasing strata height, and was observed in all subfamilies. Analyses on the relationship between forewing length and strata revealed significant result for both male and female of Satyrinae, while for body design, it was only significant for male Nymphalinae and female Satyrinae. Overall, the study on strata preference of the nymphalids had led to a better understanding on their dependence on microclimatic conditions, as well as the status of their habitat.